Methodology who needs it? - Hammersley, Martyn (London : SAGE, 2011)
In this book, Hammersley argues that, in large part, the role of methodology reflects and is part of a wider problem: the gradual decline of a previously influential academic model of inquiry. This has occurred as a result of ideological challenges and the erosion of the institutional conditions that support academic work.
Includes bibliographical references and index.
Specialized.
Description based on print version record.
Keywords: elektronické knihy; electronic books; Social sciences -- Research -- Methodology